Exploring the language agenda through purposive communication - Dungca, Catherine M.; Hermocilla, Martin Ceazar M.;Gutierrez, Ken Russel Z.;Alcoreza, Enriqueta E. (Malabon City, Philippines : Jimczyville Publications, 2019)
This book caters to one of the General Education Core Courses in the New General Education Curriculum (CMO 20, s.2013) which is Purposive Communication. It is specifically designed to equip students in developing different facets of their communicative ability such as speaking and writing and at the same time foster learning of cultural and intercultural awareness to effectively function in a local and global context.
Module 1. The basic of communication -- Module 2. Bridging the cross-cultural gap through intercultural communication -- Module 3. On, between and beyond lines! -- Module 4. The technology and the communication -- Module 5. Communication for different purposes.
Includes bibliographical references.
Keywords: COMMUNICATION